A novel active tendon pendulum tuned mass damper and its application in transient vibration control. (January 2023) - Ershadbakhsh, Amir Mohsen; Ghorbani-Tanha, Amir K.; Fallahi, Reza
Abstract: Enhancing the performance characteristics of Tuned Mass Dampers (TMDs), in particular extending their narrow frequency band of operation, has been the subject of many researches. In the adaptive type of TMDs, the device's properties can be adjusted gradually in response to a slight alteration in the excitation characteristics and physical properties of the main structure. A novel vibration absorbing system, namely Active Tendon Pendulum TMD (AT-PTMD), is proposed in the present study. The device consists of a simple pendulum whose horizontal movement is restricted by a tendon with an adjustable tensile force which is attached to the pendulum's rod. The device is designed and formulated, and its efficiency is assessed numerically and experimentally. For this purpose, a 3-degree of freedom structure is considered. Scrutinizing the responses of the uncontrolled, passively controlled and actively controlled structure shows the appropriate performance of the AT-PTMD in comparison with the passive TMD system in transient vibration reduction, particularly in reducing the total vibrational energy of the structure's response. Considering the achieved results, the proposed AT-PTMD system is capable of reducing the maximum displacement and acceleration of the main structure up to 43% and 37%, respectively, which substantiates its excellence over the common passive vibration absorbing devices. The case study also proves that the utilized mechanism for adjusting the equivalent stiffness of AT-PTMD increases its operating frequency range by 105% compared to common TMDs. Unlike active structural control systems, the suggested approach will not induce structural instability in any operating mode.